Know Where You Go: Infestation Dynamics and Potential Distribution of Two Bed Bug Species (Hemiptera: Cimicidae) in Africa - Dennis M. Mbuta; Bonoukpoè M. Sokame; Fathiya M. Khamis; Komivi S. Akutse (Insects)
Bed bugs (Hemiptera: Cimicidae) are blood-feeding insects closely linked with humans and animals, causing discomfort, and posing potential threats as disease vectors. This study focuses on Cimex lectularius (common bed bug) and Cimex hemipterus (tropical bed bug), the two key species identified in Africa. Cimex lectularius infests human habitats, while C. hemipterus, more common in Africa, infests diverse habitats, including bat colonies. In our study, we investigated the infestation dynamics and distribution of bed bugs in Africa, when considering climate, habitat, and host availability using system dynamics and ecological niche modelling techniques. System dynamics modelling analyses in Kenya revealed varied infestation dynamics, with Mombasa having high C. lectularius prevalence, Nairobi having lower coexistence, and Makueni/Bomet C. hemipterus showing dominance. Across Africa, C. hemipterus prevails, especially in central and coastal areas, while C. lectularius has lower suitability, with isolated high-suitability zones. Both species coexist in central/southern Africa, parts of the east, and coastal areas in septentrional/west Africa. The Sahara’s extreme conditions challenge both bed bug species’ survival, emphasizing climate’s role in their infestation and distribution dynamics. Insights into bed bug ecology in Africa underscore the need for comprehensive pest management and public health strategies in the continent.